Volume 3: Design; Tribology; Education 2008
DOI: 10.1115/esda2008-59146
|View full text |Cite
|
Sign up to set email alerts
|

Techniques for Assessment of Wear Between Human Cartilage Surfaces

Abstract: Osteoarthritis (OA) is a disease of joints, affecting a large number of people worldwide. One of the symptoms of OA is wear of articular cartilage; it is thought that among other factors this may be due to failure of lubrication. Injection of bio-lubricants into a joint may remedy this problem. Wear of cartilage and its prevention is a focus of much interest. The present paper describes wear tests performed using cartilage on cartilage under various working conditions. Several techniques assessing wear are des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
2
7
1
Order By: Relevance
“…These results agree with the mass of GAG released into the lubricant solutions during testing. More GAG is lost from the cartilage samples tested in saline (121.1 ± 33.1 μg (mean ± SD; consistent with literature reports 39, 40 ) than from those tested in 2.8M TEG (<3 μg). Hence, use of the 2.8M TEG biolubricant minimizes cartilage surface wear.…”
Section: Discussionsupporting
confidence: 89%
“…These results agree with the mass of GAG released into the lubricant solutions during testing. More GAG is lost from the cartilage samples tested in saline (121.1 ± 33.1 μg (mean ± SD; consistent with literature reports 39, 40 ) than from those tested in 2.8M TEG (<3 μg). Hence, use of the 2.8M TEG biolubricant minimizes cartilage surface wear.…”
Section: Discussionsupporting
confidence: 89%
“…One reason for this may be that the relevant changes to the surface morphology with wear are not captured by the surface roughness measurement, as surfaces with similar roughness can have very different morphologies (Figure 5). Similar results were seen by Verberne et al 31 when comparing worn and unworn regions of a single sample of cartilage. Additional studies into how the surface morphology changes with wear and how to measure these changes may be required before profilometric measurements can be used effectively to quantify wear or surface damage.…”
Section: Discussionsupporting
confidence: 87%
“…The significant correlation between the change in surface roughness and the visual wear of a specimen offers the potential to use surface roughness measurements as a quick means for evaluating specimen wear. It was previously shown that surface roughness itself does not correlate well with wear [Verberne et al, 2009], but this study demonstrates that the change in surface roughness before and after wear does correlate to the visual wear of the specimen. If validated chemically, changes in surface roughness can be used in future testing to quickly screen proposed implant materials.…”
Section: Evaluation Of Specimen Surface Geometry For Use In Wear Testingcontrasting
confidence: 72%
“…It has previously been found that hydroxyproline content is consistent throughout the depth of cartilage and is thus an adequate means for determining the amount of wear of the tissue during the course of an experiment [Lipshitz et al, 1975]. The weight percent of hydroxyproline was found to be approximately 7.8% throughout the depth of bovine articular cartilage [Verberne et al, 2009]. Further, HPLC measurement of hydroxyproline is sensitive, accurate, and easy to perform.…”
Section: Chemical Analysismentioning
confidence: 93%